Kepuasan Konsumen Sayuran Hidroponik Di Kota Pontianak: Sebuah Analisis Customer Satisfaction Index (CSI) - Ikhsan Nudin; Eva Dolorosa; Anita Suharyani (University of Jember, 2022)
The growth of hydroponic vegetable businesses in Pontianak City drives producers to compete by improving their quality to keep old consumers and expand to new consumers. The research used a survey method with a sampling technique using non-probability techniques, with the sample taken using a purposive sampling approach. Data were analyzed using descriptive analysis methods, Importance Performance Analysis (IPA), and Customer Satisfaction Index (CSI). The Importance Performance Analysis (IPA) results explain that the attributes that must improve are the location of sales and sales promotions such as discounts and prizes. The Customer Satisfaction Index (CSI) value ranged between 0.66-0.80 by 0.79. The overall attributes of hydroponic vegetables in Pontianak City can be said to have satisfied consumers. Hydroponic vegetable producers in Pontianak City should expand their sales locations and sales promotions. For example, price discounts and bonuses for their hydroponic products. They should also maintain or improve their performance to increase consumer satisfaction with hydroponic vegetables in Pontianak City.